Dynamics of the oscillating moving load acting on the hydro-elastic system consisting of the elastic plate, compressible viscous fluid and rigid wall - Akbarov, Surkay D.; Ismailov, Meftun I. (TECHNO-PRESS, 2016)
This paper studies the dynamics of the lineal-located time-harmonic moving-with-constantvelocity load which acts on the hydro-elastic system consisting of the elastic plate, compressible viscous fluid - strip and rigid wall. The plane-strain state in the plate is considered and its motion is described by employing the exact equations of elastodynamics but the plane-parallel flow of the fluid is described by the linearized Navier-Stokes equations. It is assumed that the velocity and force vectors of the constituents are continuous on the contact plane between the plate and fluid, and impermeability conditions on the rigid wall are satisfied. Numerical results on the velocity and stress distributions on the interface plane are presented and discussed and the focus is on the influence of the effect caused by the interaction between oscillation and moving of the external load. During these discussions, the corresponding earlier results by the authors are used which were obtained in the cases where, on the system under consideration, only the oscillating or moving load acts. In particular, it is established that the magnitude of the aforementioned interaction depends significantly on the vibration phase of the system.
Keywords: hydro-elastic system; elastic plate; compressible viscous fluid; oscillating moving load; vibration; HYDROELASTIC VIBRATION; VISCOSITY; WAVES; Engineering